An Evaluation of Pattaya–Hua Hin–Bang Pu Ferry Project in Terms of Project Management - Watsawang, Jaroon (Journal of Public Administration Chiang Rai Rajabhat University, 2021)
This research aims to study the opportunities and obstacles encountered in its project management of Pattaya–Huahin–Bang Pu ferry project, and to determine the project evaluation in terms of its project management. This research is a qualitative research in which focus group discussion was used to collect and analyze focus group data. 9 key informants who were regarded as experts in the area of the Pattaya – Huahin – Bang Pu ferry project were purposively selected for participating in focus group discussion. The two focus groups consisted of 3 ferry entrepreneurs and 6 local officials in Chonburi, Petchburi and Prachuap Khiri Khan provinces. The results found that 1) the information to identify the opportunities of the ferry project based on its project management showed that there are more opportunities for business expansion in this moment. The business opportunities are embarking on a new era of tourism since today’s tourists desire to have a break from their regular daily environments and the current policy of public sectors also plays a part in driving the tourism industry of Thailand. These help to increase the business expansion (or growth) for such ferry operations. Regarding the obstacles, the ferry business is also encountering the factors of operating costs associated with the environmental costs. The ferry operations need to depend on the total energy from oil as a raw material in transportation. Meanwhile, the impact of oil price volatility on the ferry transportation is inevitable as well. 2) The analysis of the project evaluation in terms of its project management indicated that the standards of their ships’ physical areas (hulls, life-saving appliances), of personnel (helmsmen, engineer officers, seafarers, ship owners), of services provided by staff, service equity for employees and entrepreneurs, of human rights (entrepreneurs, employees), of travel activities and plans, and of social and community activities are required [for improvement]. These tend to respond the growing needs of Both Thai and foreign tourists towards their use of Pattaya – Hua Hin – Bang Pu ferry service.